Nitrogen addition overrides the effects of Stellera chamaejasme litter on the growth of Leymus chinensis and its associated mycorrhizal fungi. (2nd February 2022) - Guo, Qiang; Zhang, Ruo-Hui; Li, Xue-Li; Liu, Xiao-Wei; Li, Ya-Nan; Xing, Fu
Abstract: Rapid spread and growth of plants that are poisonous to animals produce large amounts of plant litter in degraded grasslands. Nitrogen (N) input may promote the growth of these poisonous plants and alter the rhizosphere microbes and arbuscular mycorrhizal fungi (AMF) in particular. However, it is unclear how poisonous plant litter affects the growth of palatable plants and their associated AMF in the rhizosphere and whether and how N deposition may mediate these effects. A greenhouse experiment was performed to test the combined effects of litter addition of a poisonous plant, Stellera chamaejasme, and N addition on the growth of a dominant grass, Leymus chinensis, AMF characteristics and soil properties. Litter addition significantly increased the ramet number and aboveground biomass of L. chinensis and soil available phosphorus (AP) concentration and decreased the spore density of AMF. However, the interaction of both treatments had no significant effects on traits of L. chinensis and AMF properties. Stellera chamaejasme litter positively affected L. chinensis by increasing AP and negatively affected AMF by combining balanced changes in soil nutrients and litter-induced allelopathic compositions. High N addition may alleviate soil N limitation and inhibit litter decomposition, thus overriding the litter's effects on L. chinensis and AMF. These findings imply that it is necessary to objectively and comprehensively evaluate the ecological functions of poisonous plants beyond their harmful effects on livestock. Simultaneously, N deposition should be an indispensable factor in predicting the relationships between poisonous plants and edible plants in degraded grasslands.